Front Cover. Issue 5 (May 2017) - Reynolds, Chevonne; Cumming, Graeme S.; Vilà, Montserrat; Green, Andy J.
Abstract : The cover image, by Chevonne Reynolds et al ., is based on the Biodiversity Letter Birds as key vectors for the dispersal of some alien species: Further thoughts, DOI:10.1111/ddi.12549 . Photo Credit: Dr. Dominic Henry.